(untitled) (Modern American Journal of Biological and Environmental Sciences, 2025)
This article presents data on the effect of different sowing dates and norms on the height and number of leaves of the soybean varieties "Madad" and "Sevinch" and their analysis. When the soybean varieties were sown 10 days later than the early sowing date (25.04-30.04), the height was lower by 10.9-10.0-7.0 cm, and when sown 20 days later, it was 24.2-28.8-14.0 cm. Soybean was sown early and the sowing norm was increased by 15 kg (60 kg) compared to 45 kg per hectare, the height was increased by 4.6 cm, by 30 kg (75 kg) by 5.2 cm, when sown in the middle sowing date by 5.5-9.1 cm, and when sown late by 6.4; It is reported to be 15.4 cm height.